Analysis of responses to effects of COVID-19 pandemic on diets of urban slum dwellers in Nairobi, Kenya - Onyango, Kevin Omondi; Kariuki, Lilian W.; Chege, Christine Gacheri Kiria; Lundy, Mark (Informa UK Limited, 2024)
The COVID-19 pandemic and associated policy responses disproportionately affected low-income households in Nairobi, Kenya. This study sought to provide empirical evidence on the responses of urban slum dwellers to the impact of COVID-19 on their diets and to determine the effectiveness of these responses. The study used four-wave balanced panel data collected during the pandemic from 437 households in Kibera and Mathare slums. To answer the research questions, the study calculated household Food Consumption Scores from the 7-day food consumption data, together with other socio-economic indicators collected in the surveys. Triangulation was also done using Key Informant Interviews with community leaders. The study employed a combination of descriptive analysis and Fixed Effects model to analyze the survey data, and content analysis for key informant data. Results show that during the COVID-19 pandemic, only 38% of slum dwellers had consistently acceptable diets, while another two-thirds (61%) of the households fluctuated between acceptable and unacceptable diets, indicating the vulnerability of urban slum dwellers’ diets to food system shocks such as the COVID-19 pandemic. Household response strategies included changing consumption behavior, reorganizing household finances, reducing urban household size, prioritizing children’s access to food, relying on social networks, and relying on household food production. Some coping strategies were ineffective in improving the dietary intake of urban slum dwellers. However, changing consumption behavior by eating less preferred foods was associated with improved dietary intake. Conversely, changing consumption behavior by skipping meals, eating less variety of foods, and reducing urban household size were negatively associated with improved dietary intake. The study also finds that self-employment to generate higher income played a critical role in improving the diet of slum dwellers during the COVID-19 pandemic. The findings suggest that targeted strategies to stabilize livelihoods, incomes, and food access are critical to building resilience and responding to food system crises.